Management of peripartum intra‐abdominal hypertension and abdominal compartment syndrome. (18th June 2019) - Lozada, M. James; Goyal, Varun; Levin, Danielle; Walden, Rachel L.; Osmundson, Sarah S.; Pacheco, Luis D.; Malbrain, Manu L. N. G.
Abstract: Normal pregnancy leads to a state of chronically increased intra‐abdominal pressure. Obstetric and non‐obstetric conditions may increase intra‐abdominal pressure further, causing intra‐abdominal hypertension and abdominal compartment syndrome, which leads to maternal organ dysfunction and a compromised fetal state. Limited medical literature exists to guide treatment of pregnant women with these conditions. In this state‐of‐the‐art review, we propose a diagnostic and treatment algorithm for the management of peripartum intra‐abdominal hypertension and abdominal compartment syndrome, informed by newly available studies.